2. EXAMINATION OF MEDICAL TOURISM INTENTION AMONG TOURISTS COMING TO KHANH HOA PROVINCE, VIET NAM (Vietnam Journal of Community Medicine, 2024)
Objectives: To examine the medical tourism intention among tourists coming to Khanh Hoa Province and related factors that affect their travel intention for medical purpose.Methods: A cross-sectional design was applied with a sample of 400 tourists who resided in 4-star or higher hotels located in Khanh Hoa Province. MEDTOUR scale was used to measure the medical tourism intention which compose of three dimensions: subjective norm, attitudes, and perceived control. T test, ANOVA were used to compare means of MEDTOUR and its dimensions according to related factors. Boxplots were created to visually illustrate the differences. R software was applied to analyze data and create related graphs.Results: Means of the MEDTOUR scale and its three dimensions were larger than 3.4, indicating that tourists in the sample expressed their intention for medical purpose. There was no evidence of gender difference in medical tourism intention. However, regarding subjective norm, the result showed means of this dimension were significant low in women compared to men. Age groups and nationality were shown no significant difference in medical tourism intention.Conclusions: Tourists who came to Khanh Hoa Province expressed their intention for medical purpose but not in a very high level according to 5-point Likert scale. There was no significant difference in medical tourism intention by gender. However, encouragement and expectation from friends and relatives were not high among female compared with male tourists. There was no significant difference in the intention relating to age groups and nationality of tourists.
Keywords: Medical tourism, intention, MEDTOUR, Khanh Hoa Province.